Develop collaborative support model to boost employment opportunities for students on spectrum. Issue 8 (March 2015) - Meeks, Lisa; Westlake, Garret
<x xml:space="preserve">Abstract</x> Individuals with autism spectrum disorder are attending college in record numbers. Unfortunately, completing a college degree does not appear to improve employment outcomes for individuals with ASD, and many find it difficult to both acquire and retain jobs.